2017
DOI: 10.1093/ageing/afx035
|View full text |Cite
|
Sign up to set email alerts
|

The growing challenge of major trauma in older people: a role for Comprehensive geriatric Assessment?

Abstract: In this commentary article, we describe the impact that an ageing population is having on the nature of major trauma seen in emergency departments. The proportion of major trauma victims who are older people is rapidly increasing and a fall from standing is now the most common mechanism of injury in major trauma. Potential barriers to effective care of this patient group are highlighted, including: a lack of consensus regarding triage criteria; potentially misleading physiological parameters within triage crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…Given the complex ongoing healthcare needs of older injured patients, particularly in the setting of cognitive impairment and polypharmacy, it has been suggested that a comprehensive geriatric assessment may result in better outcomes. Furthermore, older patients managed at trauma centres that treat a higher proportion of older people with injury have been shown to have lower in‐hospital mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complex ongoing healthcare needs of older injured patients, particularly in the setting of cognitive impairment and polypharmacy, it has been suggested that a comprehensive geriatric assessment may result in better outcomes. Furthermore, older patients managed at trauma centres that treat a higher proportion of older people with injury have been shown to have lower in‐hospital mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence to directly support this approach in patients with rib fractures, recent changes to the Major Trauma Best Practice Tariff in England have aimed to incentivise the integration of geriatricians into the care pathway for older trauma patients. Data evaluating the impact of this change are awaited, but it seems plausible that routine frailty screening and early initiation of a complex geriatric assessment may influence trauma outcomes 51…”
Section: Where Should This Man Be Admitted?mentioning
confidence: 99%
“…[3][4][5] Geriatric trauma patients are more likely than their adult counterparts to die at a given Injury Severity Score as a result of their increased medical complexity (pre-existing comorbidities, concomitant medications, altered physiology and fragility) and a lack of research specific to geriatric trauma patients. [6][7][8][9] Given this challenge, the American College of Surgeons released the Geriatric Trauma Management Guidelines in 2013, which encourages trauma teams to take a multidisciplinary approach to the geriatric trauma patient and, when available, include a geriatric consultation in their management. 10 Research following this recommendation has mixed conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The geriatric consultation model is favored, because it makes the most generalizable and efficient use of geriatric specialists and hospital resources. 7,[14][15][16] Individual studies of these geriatric consultations often report improved clinical outcomes, but meta-analyses show no or fewer positive outcomes than the original literature suggests. 11,[16][17][18][19] The purpose of the present study was to analyze the effectiveness of a geriatric trauma service that is integrated into the trauma surgery workflow rather than a separated consultation service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation